HAEMATOLOGICAL PROFILE AND MENTZER INDEX IN PEDIATRIC PATIENTS PRESENTING WITH ANEMIA - AGGARWAL, ADITYA; MODI, AMIT KUMAR; K, RIMI SINGH; JHA, AVINASH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to analyze clinical and hematological profile of children with anemia and determine the Mentzer index of all cases presenting with anemia. Methods: This was a cross-sectional observational study conducted in the Department of pediatrics of a tertiary care medical college. Eighty pediatric age group patients diagnosed to be having anemia on clinical examination were included in this study. Demographic details such as age and gender were noted in all cases. A through history was obtained and a clinical examination was done. Presenting complaints were also noted. Complete blood count with peripheral blood smear examination was done in all cases. The Mentzer index was determined from complete blood count reports. Results: Out of 80 studied cases, there were 57 (71.25%) boys and 23 (28.75%) girls. The mean age for boys was 9.12±3.14 years and for girls, it was slightly higher at 10.24±3.46 years. Fatigue (73.75%), pallor (71.25%), and anorexia (56.25%) were common complaints. About 55% had mild anemia 22.5% had moderate anemia and 22.5% suffered from severe. Mean hemoglobin concentration of studied cases was found to be 8.42±3.98 g/dL. The most prevalent blood picture was the normocytic normochromic blood picture, representing 60% of cases. Mentzer index ranged from a minimum of 10.83 to a maximum of 27.76, with the mean value being 17.40±2.92. Notably, the vast majority of patients (97.5%) had a Mentzer Index >13, suggesting a high prevalence of iron deficiency. Conversely, only 2.5% of the patients had a Mentzer Index at or below 13, indicating a much smaller subset in whom Hb electrophoresis was needed to rule out thalassemia trait. Conclusion: Although most of the children with anemia are secondary to iron deficiency Mentzer index should be determined in all patients of anemia so as to avoid inadvertently prescribing iron supplementation in cases of thalassemia trait.